Macroeconomic Indicators and Economic Growth in West Africa: Evidence from Dynamic Panel Models - Sule, Sani Abdullahi; Hakim, Lukman; Putro, Tetuko Rawidyo; Pamungakas, Putra; Babatunde, Kazeem Alasinrin (International Journal of Economics and Financial Issues, 2025)
This study investigates the effect of macroeconomic indicators on West Africa economies where instability and external shocks constitute significant challenges. It employs dynamic panel models and the Generalized Method of Moments (GMM) procedure to account for endogeneity. The paper applied panel data from 1990 to 2022 on inflation, foreign direct investment, exchange rates, participation in the labour force, international reserves, and the COVID-19 effect. The results suggest that inflation and international reserves are major growth drivers, while exchange rate impact is minimal due to structural and governance constraints. The study, therefore, advocates for flexible monetary policies, improved regulatory frameworks, and strategic investments in human capital to foster the continent’s economic resilience.